Effect of Narcotic Analgesia on Decision to Operate in Acute Appendicitis - Muhammad Faheem Anwer, Fizza Anwar, Wasif Majeed Chaudhry, Muhammad Adil Khurshid, M. Waseem Anwar, Shahid Majeed, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To study that narcotic analgesia administration in patients of acute appendicitis does not delay the diagnosis and does not interfere with the decision to operate in these patients. Study design: A randomized cross-over study. Setting and duration of study: Study was done at surgery department of Combined military hospital Lahore over a period of two years from March 2019-2021. Methodology: It was a double-blind randomized crossover study. A total of 100 patients, who were confirmed as acute appendicitis by clinical examination, were included. All the male and female patients of age 16 years and above were included in the study. The patients were divided in two groups each having 50 patients. The drugs were labelled as drug A and drug B. Drug A was morphine and drug B was placebo. Each drug was given to both the groups by crossover with an interval of 30 minutes and the components of physical examination were analyzed for both groups. The pain score was calculated by the visual analogue scale (VAS) for both the groups at both intervals. The p-value was calculated by using student’s t-test. The frequency and percentages of the decision to operate were calculated. The data was tabulated and then analyzed on SPSS version 23. Results: The pain score was calculated for both groups of male and females. The pain score difference was calculated in both groups and then p-value was calculated which came out to be significant. The frequencies of the decision to be operated were also calculated in both the groups and the results showed that there was no effect of narcotic analgesia on the decision to operate in patients with clinically diagnosed acute appendicitis Conclusion: The use of morphine analgesia in the patients of acute appendicitis does not alter the diagnostic efficacy of the patients of acute appendicitis. Keywords: Acute abdominal pain, acute appendicitis, Narcotic analgesia, Visual analog scale (VAS)